Architectural Objects and Public Spaces Connected with Industry. A Contribution to the Discussion on Artistic and Aesthetic Values - Waryś, Ewa (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2017)
The article presents the contemporary cultural landscape of the historical workers’ settlements, located within the current administrative boundaries of the city of Katowice. Selected building complexes are standardized in terms of typology and building design, but differ in terms of the conservation status and forms of protection. The aim of the discussion is to show the relationship between the artistic and architectural aesthetics and public spaces related to the industry. The subject matter is an attempt to draw attention to the problem of the conservation status of most parts of the historical complexes of residential buildings in Upper Silesia, their untapped potential and declining values.